Tingkat Kecemasan Mahasiswa STIKES Wira Husada Dalam Menghadapi Pembelajaran Selama Pandemi Covid-19 (STIKes Surya Global Yogyakarta, 2023)
Background : Covid-19 has an impact in all various sectors. The pressure that has been going on during the Covid-19 pandemic can cause disturbances, in the form of excessive fear and anxiety for the safety of oneself and those closest to them, changes in sleeping and eating patterns, boredom and stress due to being constantly at home, difficulty concentrating, worsening physical health, the emergence of psychosomatic disorders. Student’s health must take practical lessons offline and often have to practice clinically at a hospital. It can increase the vulnerability to exposure Covid-19. They were afraid if they were infected of Covid-19, no one would take care of them, worried about their logistical needs, causing people and family members would be infected, and could not go home. This study aims to know the level of anxiety of student’s health in facing learning during the Covid-19 pandemic.Methods : This research used observational analytic method with cross-sectional approach. The populations were 480 students from STIKES Wira Husada. A sample was 218 students by using Slovin formula and taken proportionally. The data were analyzed using the Spearman Rank with a 95% degree of confidence (α=0.1).Results : The result of this study showed that the moderate anxiety levels were (56.7%), the mild anxiety levels were (43.3%), not anxious was (0%) and severe was (0%)Conclusion: The conclusion was the anxiety level of STIKES Wira Husada students in facing learning during the Covid-19 Pandemic was mostly at a moderate level of anxiety.